2015
DOI: 10.5430/jnep.v5n11p10
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationships between NCLEX-RN performance and nursing student factors, including undergraduate nursing program performance: A systematic review

Abstract: The National Council Licensure Examination for Registered Nursing (NCLEX-RN) replaced the Canadian Registered Nursing Examination (CRNE) in January 2015 as part of the requirements for qualifying for registered nurse (RN) status in all but one Canadian province. This substantial change is likely to have a profound impact on Canadian undergraduate nursing degree programs practices. This systematic review aims to examine the evidence describing the relationship between undergraduate nursing program performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…In support of this recommended strategy, it was reported that independent individual study is an essential part of the preparation to achieve high NCLEX scores ( Johnson et al, 2017 ). It was also reported that significant improvement in NCLEX pass rates was observed when computer-based examinations and intensive review drills were deployed at the end of senior year ( Park, 2018 ) and when critical thinking skills are integrated into the curriculum ( Sears et al, 2015 ;Taylor, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this recommended strategy, it was reported that independent individual study is an essential part of the preparation to achieve high NCLEX scores ( Johnson et al, 2017 ). It was also reported that significant improvement in NCLEX pass rates was observed when computer-based examinations and intensive review drills were deployed at the end of senior year ( Park, 2018 ) and when critical thinking skills are integrated into the curriculum ( Sears et al, 2015 ;Taylor, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kelulusan uji kompetensi perawat dapat dipengaruhi dari berbagai faktor. Faktor yang memiliki pengaruh signifikan terhadap kemampuan peserta untuk dapat lulus uji kompetensi ialah faktor kognitif, akademik dan individu (Sears, 2015). Menurut Kholifah & Kusumawati (2016) faktor yang mempengaruhi yaitu persiapan yang matang dengan memperkenalkan kisikisi uji kompetensi dan memberikan kesempatan untuk menjelaskan pemaparan terhadap praktik klinik.…”
Section: Pendahuluanunclassified
“…Terdapat berbagai faktor yang dapat memengaruhi tingkat kelulusan dalam mengikuti uji kompetensi. Faktor-faktor yang memiliki pengaruh secara signifikan terhadap kemampuan mahasiswa untuk lulus uji kompetensi ialah faktor akademik, faktor kognitif, dan faktor individu (Sears, Othman, & Mahoney, 2015 Berdasarkan faktor-faktor tersebut, dapat disimpulkan bahwa tingkat kelulusan mahasiswa dapat dipengaruhi oleh faktor internal (faktor yang berasal dari dalam diri individu) dan faktor eksternal (faktor yang berasal dari luar diri individu). Faktor internal terdiri atas intelegensi, kondisi psikis, kesiapan ujian, kondisi fisik, dan prestasi akademik.…”
Section: Latar Belakangunclassified